Replication Data for: "Using Facebook Targeted Advertisements to Recruit Survey Respondents" - Gemenis, Kostas (My University, 2024)
The ability to run targeted advertisements on popular social media platforms, such as Facebook, has enabled researchers to obtain quickly demographically and geographically diverse samples in response to research opportunities, at a very low cost. A shortcoming of using Facebook is that it employs algorithms to optimize ad delivery by favouring users who are most likely to click on them and, as a result, the characteristics of the end samples are likely to differ from the underlying population. The paper provides a short guide for those interested in recruiting survey participants through Facebook ads and suggestions on improving the characteristics of the end samples, especially on variables for which the ad targeting is less efficient. Empirically, the paper compares a Facebook ads sample to a gold standard (the European Social Survey) and provides open access to the replication data. The paper concludes with suggestions about the suitability of Facebook ads data for different types of research projects.
Keywords: Facebook